Ten‐year updated meta‐analysis of the clinical characteristics of pediatric mania and hypomania. (9th January 2016) - Van Meter, Anna R; Burke, Coty; Kowatch, Robert A; Findling, Robert L; Youngstrom, Eric A
Abstract : Objectives: The phenomenology and diagnosis of pediatric bipolar disorder has been controversial. We aimed to update a 2005 meta analysis of the prevalence of manic symptoms in youth, in order to determine whether the picture of pediatric mania has changed as research on pediatric bipolar disorder has grown. Methods: We conducted literature reviews in PsycINFO and PubMed; studies with the prevalence of manic symptoms in youth were included. Two raters coded each study; kappa was 0.86–1.0. Results: Twenty studies were meta‐analyzed (N = 2, 226 youths). The most common symptoms across bipolar subtypes, using a random‐effects model, were: increased energy 79%, irritability 77%, mood lability 76%, distractibility 74%, goal‐directed activity 72%, euphoric/elated mood 64%, pressured speech 63%, hyperactive 62%, racing thoughts 61%, poor judgment 61%, grandiosity 57%, inappropriate laughter 57%, decreased need for sleep 56%, and flight of ideas 54%. Symptom rates were heterogeneous across samples; potential predictors were explored but no clear patterns were found. Conclusions: Debate continues about the definitions of pediatric bipolar disorder; the results of this meta‐analysis suggest that there is significant heterogeneity of symptom prevalence between studies, and that symptoms vary widely across individuals. Understanding the roots of this heterogeneity could broaden understanding of the complex clinical presentation of pediatric mania, and aid in diagnosis.